Feasibility of Neurapheresis™ as a Therapy for Multidrug Resistant Gram-negative Bacterial Meningitis. (4th October 2017) - Ballard, Christi; Ashraf, Bilal; Ejikeme, Tiffany; Hansen, Brenda; Charalambous, Lefko; Pagadala, Promila; Sharma-Kuinkel, Batu K; Giamberardino, Charles; Hedstrom, Blake; Verbick, Laura Zitella; Mccabe, Aaron; Lad, Shivanand P; et al.
Abstract: Background: The World Health Organization has identified Pseudomonas, Acinetobacter and Klebsiella (PAK) as three multidrug resistant (MDR) gram-negative pathogens that pose a threat to human health. The greatest threat lies in hospitals, nursing homes, and patients with devices such as intravenous catheters and ventilators. Gram-negative bacterial meningitis (GBM) manifests when these bacteria invade the central nervous system. Due to the threat of increasing antibiotic resistance and the high mortality associated with MDR GBM, we have tested a closed-loop, extracorporeal cerebrospinal fluid (CSF) filtration system ( Neurapheresis TM ) for its applicability in this context. Here we demonstrate feasibility of Neurapheresis for MDR GBM and characterize system parameters for bacterial clearance. Methods: PAK cultures were grown and diluted to 1 × 10 7 cells/mL in artificial CSF or Luria-Miller broth. Both single pass and closed loop filtration were performed with various tangential flow filtration (TFF) and dead-end filter paradigms. Samples were taken either immediately post-filter or after every full CSF volume cycle (150 mL) during a long-term closed loop experiment. Bacterial load, endotoxin and cytokines were quantified. Results: In single pass tests, 5kDa and 100kDa TFF filters and 0.2µm and 0.45µm dead-end filters excluded all PAK organisms completely. The 100kDa and 5kDa TFF filters significantly reduced endotoxin concentration by >95% and >99% of baseline, respectively. The 5 kDa TFF filters produced a 2-log (>99%) reduction in cytokines (IL-1ra, IL-6, TNF, CRP, and CXCL10). In closed-loop experiments, both TFF filters demonstrated a 1–2 Log CFU (90–99%) reduction of all PAK organisms over 4 filtration cycles. Conclusion: Neurapheresis shows potential to be an efficient multi-modal tool for controlling and treating MDR GBM in this in vitro model. Extending closed loop filtration over time demonstrates capability for rapid sterilization of the CSF. Future iterations may include adjunctive intrathecal drug delivery to further accelerate elimination of bacteria. Reduction of both endotoxin and cytokines by Neurapheresis may have significant implications for controlling the damaging neuro-inflammatory response during MDR GBM. Disclosures: B. Hedstrom, Minnetronix, Inc.: Employee, Salary; L. Zitella Verbick, Minnetronix, Inc.: Employee, Salary; A. Mccabe, Minnetronix, Inc.: Employee, Salary; S. P. Lad, Minnetronix, Inc.: Collaborator and Scientific Advisor, Licensing agreement or royalty, Research grant and Research support; V. Fowler Jr., Pfizer, Novartis, Galderma, Novadigm, Durata, Debiopharm, Genentech, Achaogen, Affinium, Medicines Co., Cerexa, Tetraphase, Trius, MedImmune, Bayer, Theravance, Cubist, Basilea, Affinergy, Janssen, xBiotech, Contrafect: Consultant, Consulting fee; NIH, MedImmune, Cerexa/Forest/Actavis/Allergan, Pfizer, Advanced Liquid Logics, Theravance, Novartis, Cubist/Merck; Medical Biosurfaces; Locus; Affinergy; Contrafect; Karius: Grant Investigator, Grant recipient; Green Cross, Cubist, Cerexa, Durata, Theravance; Debiopharm: Consultant, Consulting fee; UpToDate: Royalties, Royalties